Working capital management and performance: A literature review investigation of a non-linear relationship. - Al-Maktoumi, Iman; Supian, Kamisah; Albada, Ali (International Journal of Accounting, Finance and Business, 2024)
This study discusses the importance of working capital management (WCM) in determining a firm’s financial performance. Furthermore, the paper highlights a non-linear relationship between working capital and profitability, with a concave relationship indicating that working capital has a positive effect on profit up to an optimum level, after which it negatively affects profitability. This study suggests that proactive working capital policies can enhance profits and provide corporate policy implications for maximizing financial performance. Moreover, the study highlights the importance of maintaining working capital at an optimal level to benefit shareholders and suggests that working capital can be used as a tool to optimize financial performance and identify areas for improvement. Overall, the research contributes to understanding treasury management and emphasizes the importance of effectively managing working capital for profit maximization..